JILBAB DALAM AL-QUR’AN DAN AL-HADITS SERTA APLIKASINNYA PADA PENDIDIKAN ISLAM PERSPEKTIF TEORI HABITUS PIERRE BOURDIEU - Katni Katni (Universitas Muhammadiyah Ponorogo, 2017)
Hijab is long jumpsuit that covers the entire face except for physical wrists and feet wore by Muslim women. The headscarf is prescribed in Islam to instill a thorough tradition (universal) and critical in uprooting the roots of moral damage was bad. Laws of hijab or clothing its essence is to close the Association. the terms jilbab/clothing for Muslim women is the following: first, was labeled a cover the whole body except the face and palms. Second, Loose so as not to dazzle the shape of a woman's body. Third, clothes or a scarf made from fairly thick so it can hide the underlying flesh and skin color and shape of a woman's body. Fourth, no flashy colored the same, meaning that by showing off the body and draw the attention of others. Fifth, do not resemble the clothing of women non-Muslims or infidels sixth, did not resemble the clothing of men. Educational applications veiled and dressed in an Islamic perspective on the education theory of Habitus Piere Borde have great opportunities and relevant thing to do on the development of education dressed and veiled good institution formal education such as school/madrasah of levels of primary, secondary or higher education. It can also be conditioned through informal education at home and the Muslim community, so the trend created through policies, rules or habits will be firmly entrenched in the hearts of Muslimah, and perceptions the structured model in mind, the clothes he wore, bought and not easily deterred by the current negative culture from outside. Habitus veiled and dressed can be passed down to the next generation so that the generation born astrology al-Kitab and dressed in the Islamic community in forming the main Islam approves by Allah SWT.